2009
DOI: 10.1111/j.1398-9995.2008.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin testing in patients with hypersensitivity reactions to iodinated contrast media – a European multicenter study

Abstract: Skin testing in patients with hypersensitivity reactions to iodinated contrast media -a European multicenter study Iodinated contrast media (CM) are highly concentrated solutions of iodinated benzene derivatives, used to enhance X-ray procedures (1). Although these products are regarded as relatively safe, they are known to cause both immediate ( £ 1 h) and nonimmediate (>1 h) hypersensitivity reactions in susceptible individuals (2).Background: Iodinated contrast media cause both immediate and nonimmediate hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
332
4
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(378 citation statements)
references
References 29 publications
20
332
4
22
Order By: Relevance
“…Several studies support the finding of specific IgE-mediated immunological mechanisms in immediate reactions, and positive skin test results with ICM have been reported in patients who experience severe immediate reactions [14][15][16]. Some of these patients also react to other ICM to which they had not been previously exposed, probably because the core chemical structure common to ICM is part of the antigenic determinant and thus induces cross-reactivity.…”
Section: Immediate Reactionsmentioning
confidence: 67%
See 3 more Smart Citations
“…Several studies support the finding of specific IgE-mediated immunological mechanisms in immediate reactions, and positive skin test results with ICM have been reported in patients who experience severe immediate reactions [14][15][16]. Some of these patients also react to other ICM to which they had not been previously exposed, probably because the core chemical structure common to ICM is part of the antigenic determinant and thus induces cross-reactivity.…”
Section: Immediate Reactionsmentioning
confidence: 67%
“…Several studies of nonimmediate reactions to ICM have shown skin tests to be positive with the ICM involved [15,60,67,68] and with other ICM with similar chemical structures [15,19].…”
Section: Nonimmediate Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although skin testing may be used to confirm a reaction to an ICA, the sensitivity of the test may depend on the duration of the administration of the test compared with the timing of initial ICA exposure. 47 Furthermore, a negative predictive value of 97% suggests that skin testing may be more useful to rule out a reaction to ICAs. 48 In patients with a prior reaction, ICAs should be avoided, if possible.…”
Section: Delayed Reactions To Contrast Agentsmentioning
confidence: 99%